OPTIMIZATION OF CULTIVATION CONDITIONS FOR RECOMBINANT INFLUENZA A/H5N1 STRAINS EXPRESSING BRUCELLA SPP. ANTIGENS (L7/L12, OMP16, OMP19, CU-ZN-SOD) - Yesimbekova, N.B.; Duisenbayev, B.D.; Keramatdinova, A.M.; Kartbay , G.K.; Yershebulov , Z.D.; Ryskeldinova , Sh.Zh.; Absatova , Zh.S. (Eurasian Journal of Applied Biotechnology, 2026)
The study presents the results of optimizing cultivation conditions for recombinant influenza A/H5N1 strains (NS1-truncated) expressing Brucella spp. antigens (L7/L12, OMP16, OMP19, CU-ZN-SOD). MDCK and Vero cell lines were used in the experiments. The effects of the infectious dose, incubation temperature, cultivation duration, as well as the effect of protease on viral replication, were determined. It was found that the optimal conditions for cultivating recombinant influenza A strains expressing Brucella antigens are the use of MDCK cell culture, an infectious dose of 0.01 TCID50/cell, an incubation temperature of 34.0±0.5 °C, a cultivation period of 48 hours, and addition of Trypsin-TPCK at a concentration of 1.5–2.0 μg/mL. Under these conditions, viral infectivity reached ≥5.75 log TCID50/mL, and the hemagglutination titer was 1:32. The genetic stability of the viral constructs was maintained for at least four consecutive passages. The obtained results can be used in the development and scale-up of influenza vector vaccine production technology.